A case report of spontaneous biliary peritonitis with accessory liver lobe: rare presentation of a rare pathology - Das, Bhuban M.; Ethiraj, Suraj; Mohanty, Sujit K.; Mohapatra, Ramapada (International Surgery Journal, 2021)
Spontaneous intrahepatic bile duct perforation with associated accessory liver lobe is an exceedingly rare condition with very few cases reported in the literature. Here we report a case of 76 years old man presenting with severe pain, abdominal distension since 3 days having jaundice and signs of peritonitis. Having undergone an exploratory laparotomy, 1 liter of bilious peritoneal fluid was seen with a perforation of left intra hepatic bile duct with a presence of an accessory lobe of liver. The gall bladder was contracted with multiple stones. Extrahepatic biliary duct was found normal intraoperatively. A cholecystectomy with resection of the accessory liver lobe was done. Post operatively patient had persistence of jaundice for which a magnetic resonance cholangiopancreatography was done, revealing a distal common bile duct calculus. Patient underwent endoscopic retrograde cholangiopancreatography with stone extraction on post operative day 10 relieving the symptoms. Patient is on regular follow up with no further complications. Awareness of such unusual occurrences is necessary for early diagnosis and instituting the appropriate treatment thereby reducing the mortality.